2010
DOI: 10.1210/er.2009-0041
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Human Reproductive Health

Abstract: Via its interaction in several pathways, normal thyroid function is important to maintain normal reproduction. In both genders, changes in SHBG and sex steroids are a consistent feature associated with hyper- and hypothyroidism and were already reported many years ago. Male reproduction is adversely affected by both thyrotoxicosis and hypothyroidism. Erectile abnormalities have been reported. Thyrotoxicosis induces abnormalities in sperm motility, whereas hypothyroidism is associated with abnormalities in sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
765
5
83

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,017 publications
(924 citation statements)
references
References 374 publications
26
765
5
83
Order By: Relevance
“…В подальшому ці гормони беруть участь у фор-муванні механізмів адаптації, впливають на ріст і фізичний розвиток дитини [7,8]. Під час вагітності на організм жінки має вплив низка специфічних для цього стану чинників, які можуть призвести до зна-чної стимуляції ЩЗ [9,10].…”
Section: вступunclassified
See 2 more Smart Citations
“…В подальшому ці гормони беруть участь у фор-муванні механізмів адаптації, впливають на ріст і фізичний розвиток дитини [7,8]. Під час вагітності на організм жінки має вплив низка специфічних для цього стану чинників, які можуть призвести до зна-чної стимуляції ЩЗ [9,10].…”
Section: вступunclassified
“…У регіонах із дефіцитом йоду поширеність ди-фузного нетоксичного зоба (ДНЗ) у другій половині вагітності досягає 80 % [2][3][4]. Тому перебіг вагіт-ності та пологів у жінок із ДНЗ привертає все біль-шу увагу акушерів-гінекологів.…”
Section: вступunclassified
See 1 more Smart Citation
“…The prevalence of hypothyroidism during pregnancy is estimated to be 0.3-0.5% for overt hypothyroidism (OH) and 2-3% for subclinical hypothyroidism (SCH). Thyroid antibodies are found in 8-14% of women in the childbearing age, and chronic autoimmune thyroiditis is the main cause of hypothyroidism during pregnancy, apart from iode deficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Krassas et al (2010) recently reported TSH reference ranges: 5th percentiles for the second and third trimesters were 0.03–0.39 and 0.13 mIU/L, respectively, suggesting that the cutoffs used by Chevrier et al (2010) led to an incorrect classification of at least some women.…”
mentioning
confidence: 99%